GIS and remote sensing based assessment of West Rapti River channel migration in Nepal - Sandesh Gharti; Prabin Poudel; Ramesh Silwal; Suchana Baniya; Jeetendra Gautam; Om Mishra; Sijan Bista; Dipendra Dhungana (Discover Water)
Abstract Abrupt changes in climatic conditions trigger river channels to migrate laterally due to changes in surface water conditions. West Rapti River in the Terai, a flat geographic region of Nepal with high mountains and Chure Hill on the north, is highly susceptible to water-induced disasters. Geographical Information System and Remotely Sensed Imageries were used to analyze the spatio-temporal changes of West Rapti River between 1990 and 2023, to assess their impact within the approximately 53 km range of Deukhuri Valley (Dune Valley). Using freely available Landsat satellite imagery we extracted water surface features through the Normalized Difference Water Index and generated 27 cross-sections (CS) to track channel shift. Those cross-sections were generated in the gap of 2000 m using the River Bathymetry Toolkit (RBT) to assess the Sinuosity & Braiding Index of the river channel within the planform. This study found that river channels migrated laterally determined as significant shifts, notably 1.43 km towards the northeast within CS-23 and 0.72 km towards the south direction within CS-25 in the last 33 years. Nearly no shifting impact was observed from CS-12 to CS-17 showing embankment and mitigation efforts being effective within this range. The study shows the river is naturally multi-channeled and exhibits a braided pattern with sinuosity index values ranging from 1.02 to 1.38, indicating highly braided conditions during 2010 and 2015. The river channel was found to be driven by a high sediment deposit of about 15.35 Sq. km across the 53 km range. These results are crucial for formulating integrated river basin management plans in the West Rapti River basin laying the foundation for future research to explore sustainable river management practices in the future.